1972
DOI: 10.1111/j.1538-4632.1972.tb00472.x
|View full text |Cite
|
Sign up to set email alerts
|

The Weber Problem: Solution and Interpretation*

Abstract: In location theory, the so-called "Weber Problem" has been especially cherished by a large number of authors. It has been generalized, extended, reformulated, criticized, but never forgotten. I intend to present in this paper a trigonometric solution to the triangle problem. An attempt also will be made to extend it to the general polygon case. In the second part, the concept of the "ideal weight" will be modified in order to extend the scope of Weberian theory beyond the sole consideration of transportation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…Then, the minimum point can be found by defining the components of equation (5) but it coincides with the Weber point only in the special case of an equilateral triangle. Further contrasts between the behavior of P and the Weber point are indicated by comparison with the results obtained by Tellier (1972). To compare the properties of P with that of the centroid, which minimizes the sum AP2 + BP2 + CP', note that the centroid divides AU in the ratio of 2:1, and similarly for BV and CW.…”
Section: Definitions Of Termsmentioning
confidence: 97%
See 1 more Smart Citation
“…Then, the minimum point can be found by defining the components of equation (5) but it coincides with the Weber point only in the special case of an equilateral triangle. Further contrasts between the behavior of P and the Weber point are indicated by comparison with the results obtained by Tellier (1972). To compare the properties of P with that of the centroid, which minimizes the sum AP2 + BP2 + CP', note that the centroid divides AU in the ratio of 2:1, and similarly for BV and CW.…”
Section: Definitions Of Termsmentioning
confidence: 97%
“…Let ( P I , P2), (al, a2), (bl, b2), and (cl, c2) be the coordinates of points P, A, B , and C respectively. Then, the minimum point can be found by defining the components of equation (5) Tellier (1972). To compare the properties of P with that of the centroid, which minimizes the sum AP2 + BP2 + CP', note that the centroid divides AU in the ratio of 2:1, and similarly for BV and CW.…”
Section: (5)mentioning
confidence: 99%
“…A well‐known continuous‐space optimization approach is the Weber problem (Drezner, Klamroth, Schobel, & Wesolowsky, ; Tellier, ; Wesolowsky, ), involving the identification of a point (e.g. a factory) to minimize the total transportation costs to a finite number of demand locations (e.g.…”
Section: Spatial Optimization Modelsmentioning
confidence: 99%
“…For cases with three demand locations, the problem is sometimes referred to as the Fermat problem (Wesolowsky, ) and can be solved using a geometrical approach to the triangle problem (Simpson, ). For cases of more than three demand points, geometrical approaches become infeasible and the problem is commonly solved by an iterative method called the Weiszfeld algorithm (Church & Murray, ; Drezner et al., ; Tellier, ).…”
Section: Spatial Optimization Modelsmentioning
confidence: 99%
“…The goal is to find the location that 4 minimizes the sum of the weighted transportation costs. Direct numerical solutions have been developed (Weiszfeld 1937, Tellier 1972. The work by Vardi and Zhang (2001) showed that a modified version of Weiszfeld's algorithm for solving the Weber problem converged monotonically to a unique solution.…”
Section: Related Workmentioning
confidence: 99%